The biomedical applications of graphene. Issue 3 (6th June 2018) - Edirisinghe, Mohan
Abstract : This issue of Interface Focus is a collection of papers on 'The biomedical applications of graphene'. The idea to put together this theme issue evolved during discussions between Prof. Peter N.T. Wells CBE, FREng, FMedSci, FRS and myself in mid-2016. Very sadly, about a year ago, Prof. Wells passed away. However, before that and even in the various last stages of his life he was intensely involved in planning this theme issue with me. I am deeply indebted to him for his contributions towards this and I dedicate this theme issue to him as a memorial.